1990
DOI: 10.1080/00223980.1990.10543212
|View full text |Cite
|
Sign up to set email alerts
|

Assertiveness and Social Anxiety in Chinese-American Women

Abstract: The notion that Chinese Americans, compared to Caucasian Americans, are passive and nonassertive was examined with self-report and behavioral measures. Chinese-Americans (n = 36) and Caucasian (n = 19) female college students were randomly assigned to one of two conditions: role-playing a series of 13 situations requiring assertion with an Asian experimenter or role-playing the same situations with a Caucasian experimenter. The Chinese-American students were as assertive as the Caucasian subjects on all behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
22
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 30 publications
11
22
0
Order By: Relevance
“…Using the assertive-narcissistic participation distinction, we may also reconcile the apparent contradiction of no AH-EH difference in behavioral assertiveness (Sue et al, 1983;Sue et al, 1990) with our findings of large AH-EH differences in classroom participation. That is, students of Asian heritage are assertive but not narcissistic.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Using the assertive-narcissistic participation distinction, we may also reconcile the apparent contradiction of no AH-EH difference in behavioral assertiveness (Sue et al, 1983;Sue et al, 1990) with our findings of large AH-EH differences in classroom participation. That is, students of Asian heritage are assertive but not narcissistic.…”
Section: Discussionsupporting
confidence: 56%
“…Direct measurement of relevant behaviors, however, is rare. Interestingly, the only two known studies -both by Sue and colleagues --found no behavioral differences in laboratory simulations of shyness situations (Sue, Ino, & Sue, 1983;Sue, Sue, & Ino, 1990 but see Grimm & Church, 1999). Such method artifacts can be ruled out by collecting cross-method convergent evidence, particularly with concrete measures of behavior.…”
Section: Studymentioning
confidence: 99%
“…As such, some Asian American parents may have difficulty expressing their needs and opinions about services in public forums. This result confirmed the findings of previous studies that some Asian American individuals were more apprehensive about social situations than their non-Asian American cohorts (Sue et al, 1990), and that they consequently participated less in social/medical service processes than non-Asian American individuals (Young & Klingle, 1996). The Requesting Help scale reflects one's willingness to ask for reasonable favors and help (Mauger & Adkinson, 1980).…”
Section: Discussionsupporting
confidence: 88%
“…Such measurement error could be ruled out by collecting cross-method convergent evidence of social anxiety (e.g., role-playing tests, collecting unobtrusive observations of classroom participation, and event-contingent experience sampling methodology). Future research should examine whether the ethnic/ cultural differences found on the SAS-A are also evident using behavioral indexes of social anxiety; some studies comparing Asian American and White American college students on behavioral aspects of social anxiety have not found ethnic differences [59].…”
Section: Discussionmentioning
confidence: 99%